The effect of chromium added into basal diet on serum total protein, urea, triglyceride, cholesterol and serum and tissue chromium, zinc, copper levels in rabbits - Şahin, Kazım; Güler, T; Şahin, Nurhan; Ertas, ON; Erkal, N (Scientific Technical Research Council Turkey, 1999)
This study was conducted to determine the effect of supplemantal dietary chromium on serum total protein, urea, triglycerides, cholesterol, and serum and tissue chromium, time, and copper contents of pregnant rabbits, their offspring and their young rabbits. Treatment groups consisted of chromium level as follows: Control Group no supplementation chromium into basal diet, Treatment 1 (200 ppb Group) contained 200 ppb of supplemental chromium into basal diet, and Treatment II (400 ppb Group) contained 400 ppb of supplemental chromium into the basal diet which contained 539.17 ppb chromium. For this purpose, at the begining of the study, 36 rabbits were assigned to 3 treatments. Blood and tissue were collected from pregnant rabbits before birth, from their offsprings before weaning and from weaning before mature. Serum total protein, urea, triglyceride, and cholesterol were analyzed using biochemistry analyzer. Diets, serum and tissue were analyzed for chromium, zinc, and copper using atomic absortion spectroscopy. Supplemental chromium had no effects (P>0.05) on serum total protein, urea, triglycerides, cholesterol levels in all generations. On the other hand, supplemental chromium increased (P<0.05) serum, liver, kidney, lung and muscle, zinc levels in all generations of rabbits fed diets suplemented with chromium, but decreased copper levels. The results of this investigation indicated that chromium supplementation to basal diet had synergistic effect on zinc levels but antagonist effect on copper levels.
Keywords: chromium; protein; triglycerides; cholesterol; zinc; copper; rabbits